Analisis Faktor-Faktor Yang Mempengaruhi Kesiapan UMKM Dalam Menerapkan SAK-EMKM - Maya Aresteria; Apip . (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
This study was conducted to examine the factors that influence the readiness of SMEs in implementing reports according to SAK-EMKM. The purpose of implementing SAK EMKM is expected to provide an overview of the performance of MSME management, as well as financial reports in the past and a picture of the future, so that they can be trusted and relied on by both the management, MSME members, and external parties who have interests related to MSMEs. The results showed that only the socialization variable of SAK EMKM had a significant effect on the readiness of SMEs to apply SAK EMKM. While the variables of owner's education level, business scale, business age do not have a significant effect on the readiness to implement SAK EMKM in MSMEs.